Wayfarer - Bracken, Alexandra (Bracken, Alexandra. Passenger series ;, 2017)
Robbed of the powerful object she needed to save her mother, time traveler Etta Spencer is stranded far from home and the privateer she loves before resolving to destroy the astrolabe, a mission that is challenged by a shattering revelation.